Incorporating WhatsApp to Increase Writing Skills of the Tenth Graders - Hamzah, Mohammad Amir; Dibdyaningsih, Haris; Syafi'i, Ahmad (New Language Dimensions, 2023)
This study reviews the effect of incorporating WhatsApp to develop self-introduction writing skills of tenth graders. The purpose of this study is to investigate whether there is a positive effect on students’ writing skills. This research design used an embedded mixed method design the main research design is a nonrandomized control group, posttest-only design, and supported with descriptive qualitative. This study was implemented on twenty-four students of one public senior high school in Sidoarjo majoring in Science Program. Furthermore, the post-test was used to determine the learning outcome of the experimental and control groups. The test has already been validated. The technique of data analysis applied t-test by the prerequisite normality and homogeneity test. The result of this study shows that (1) there is a positive effect on students’ skill in self-introduction by incorporating WA. The Analysis of the t-test is 6.6751 at 0.05 level significance with 22 degrees of freedom is higher than which is 2.074. As the t-test value was higher than the t-table, HO was rejected, and the alternative hypothesis (Ha) was accepted. (2) The aspects of writing in the experimental group of four (content, organization, vocabulary, and language use) were “Excellent”. But the mechanic aspect obtained “Good”. And the aspects of writing in the control group of two (content and organization) were “Excellent”. Vocabulary, language use, and mechanics are “Good”.